The Effect of the Implementation of Good Corporate Governance on the Company's Financial Performance During the Covid-19 Pandemic (Case Study on Manufacturing Companies in the Goods and Consumer Sector Listed on the IDX for the 2020-2021 Period) - Yuniarti, Rozmita Dewi; Amartya, Thariza (Program Studi Akuntansi FPEB UPI, 2024)
This study aims to determine the effect of implementing good corporate governance on company financial performance during the Covid-19 pandemic. The sampling technique uses purposive sampling measuring 46 manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange during the period 2020 to 2021. The analysis technique used is the random effect model (Ordinary Least Squares). The results of the study show that managerial ownership does not affect the company's financial performance, institutional ownership affects the company's financial performance, corporate social responsibility costs affect the company's financial performance and managerial ownership, institutional ownership, and corporate social responsibility costs simultaneously affect the company's financial performance.